Clinicopathologic Features and Clinical Outcomes of Esophageal Gastrointestinal Stromal Tumor: Evaluation of a Pooled Case Series. Issue 2 (January 2016) - Feng, Fan; Tian, Yangzi; Liu, Zhen; Xu, Guanghui; Liu, Shushang; Guo, Man; Lian, Xiao; Fan, Daiming; Zhang, Hongwei
Abstract : Abstract: Clinicopathologic features and clinical outcomes of gastrointestinal stromal tumors (GISTs) in esophagus are limited, because of the relatively rare incidence of esophageal GISTs. Therefore, the aim of the current study was to investigate the clinicopathologic features and clinical outcomes of esophageal GISTs, and to investigate the potential factors that may predict prognosis. Esophageal GIST cases were obtained from our center and from case reports and clinical studies extracted from MEDLINE. Clinicopathologic features and survivals were analyzed and compared with gastric GISTs from our center. The most common location was lower esophagus (86.84%), followed by middle and upper esophagus (11.40% and 1.76%). The majority of esophageal GISTs were classified as high-risk category (70.83%). Mitotic index was correlated with histologic type, mutational status, and tumor size. The 5-year disease-free survival and disease-specific survival were 65.1% and 65.9%, respectively. Tumor size, mitotic index, and National Institutes of Health risk classification were associated with prognosis of esophageal GISTs. Only tumor size, however, was the independent risk factor for the prognosis of esophageal GISTs. In comparison to gastric GISTs, the distribution of tumor size, histologic type, and National Institutes of Health risk classification were significantly different between esophageal GISTs and gastric GISTs. The disease-free survival and disease-specific survival of esophageal GISTs were significantly lower than that of gastric GISTs. The most common location for esophageal GISTs was lower esophagus, and most of the esophageal GISTs are high-risk category. Tumor size was the independent risk factor for the prognosis of esophageal GISTs. Esophageal GISTs differ significantly from gastric GISTs in respect to clinicopathologic features. The prognosis of esophageal GISTs was worse than that of gastric GISTs.